EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI JAGUNG DI DESA MARGA CATUR KECAMATAN KALIANDA KABUPATEN LAMPUNG SELATAN - Muhammad Husaini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to analyze the influence of production factors on a maize farming business, to get the business scale, and whether the use of a maize farming production factor has been allocatively optimum in Marga Catur Village Kalianda Sub-district of South Lampung Regency. This study was analyzed by the Multiple Linear Regression with Cobb-Douglass production function and the calculation of allocative efficiency with the Ki efficiency index. The calculation results showed that the land area variable, seeds, fertilizers, pesticides, and labors influenced positively and significantly on corn production in Marga Catur Village Kalianda Sub-district of South Lampung Regency. The calculation of the business scale is at the level of increasing return to scale. Then, the results of allocation calculation for the land area variable, seeds, and pesticides are not efficient or not at the optimal proportion of production factors use so that the addition of production factor is needed. The fertilizer variable has been efficient but it still needs the addition of production factor. While the labor variable is not efficient where the use of its production factor exceeds its optimum proportion so that the reduction of production factor is needed.